PERBEDAAN PENGARUH PENGGUNAAN MEDIA ZOOM MEETING DAN WHATSAPP TERHADAP HASIL BELAJAR DAN MOTIVASI SISWA PADA PEMBELAJARAN SPLDV KELAS X MIPA MA SIRNAMISKIN KOTA BANDUNG - Asep Martoya (Jurnal Dimensi Matematika, 2022)
This study aims to determine the effectiveness of using Zoom Meeting media and Whatsapp on student learning outcomes and motivation and its impact on learning motivation of class X Madrasah Aliyah Sirnamiskin students in Bandung. The type of approach used in this research is quantitative with a quasi-experimental method and the research design is Nonequivalent (Pretest and Posttest) Control-Group Design. The subjects in this study were students of class X-MIPA 1 as the experimental class and class X-MIPA 2 as the control class. The instruments used in this study were a description test to measure learning outcomes and a questionnaire to measure student motivation. The data analysis technique in this study used quantitative analysis in the form of statistical descriptive test, normality test, homogeneity test, and mean difference test. Based on the results of the study, it can be seen that the learning outcomes of students who use Zoom Meeting media are better than students who only use WhatsApp groups. This can be seen from the data values ​​obtained are normally distributed and the average value obtained in the experimental class 74.47 greater than the control class 68.42. In other words, the use of Zoom meeting media is more effective on learning outcomes and student motivation of mathematics students compared to using WhatsApp Group. In addition, it is also known that students' learning motivation after using the Zoom Meeting media is in the fairly high category with a score of 58.26. Keywords: Zoom Meeting Media, Whatsapp, Learning Outcomes, Student Motivation.